Dinamika Maro Bathi Sistem Nggadoh Kambing Berdasarkan Hukum Adat sebagai Upaya Mengurangi Pengangguran di Kabupaten Banyuwangi - sofi faiqotul Hikmah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
This study has three objectives: (1) To analyze the dynamics of the maro bathi system nggadoh goats based on customary law in Banyuwangi,(2) To analyze the extent to which the suitability of customary law and Islamic law related to the dynamics of maro bathi system nggadoh in Banyuwangi, (3) To analyze the extent of the contribution system nggadoh in reducing unemployment and increasing the level of welfare of Banyuwangi. This research is classified as descriptive research with qualitative data from interviews, observation, documentation, and document analysis. The results of the analysis say that the share of results or maro bathi in thesystem nggadoh is a form of profit sharing cooperation called cooperation with the principle of mudharabah muqayyadah in this case the profit sharing agreed between the two parties that does not need to be recited when the initial agreement is allowed in Islam with based on the Qur'an, Surat an-Nisa (4) verse 29 explains that in seeking a rizki we are encouraged to look for the halal obtained from commerce or trade and mutual favor. While based on the Book of Al-Muhadzab Juz I, p. 392. If what is promised is to divide profits from sales (ribhi), then that includes qirod fasid, according to the scholar Tsalasah. If what is intended is to hire people, with the cost of dividing the yield, then it is called ijaroh fasidah, which has a goat must give the cost of the missile (general) to that person (amil).